Identify the equivalent expressions of 4(2x + x – 3) – 3x + 3 by substituting x = 2 and x = 3.
2 answers:
Answer:
9
18
Step-by-step explanation:
<u>x = 2:</u>
4(4 + 2 - 3) - 6 + 3 = 12 - 6 + 3 = 9
<u>x = 3:</u>
4(6 + 3 - 3) - 9 + 3 = 24 - 9 + 3 = 18
Answer:
9x -9
9(x - 1)
4(3x-3) - 3x + 3
Step-by-step explanation:
4(2x + x-3) - 3x + 3
Combine like terms
4(3x-3) - 3x + 3
Distribute
12x -12 -3x+3
Combine like terms
9x -9
Factor out 9
9(x-1)
You might be interested in
A is the answer babygirl.
The answer is $6.38 hope this helps
36/5 will be simplified 144/20
Answer:
$6
Step-by-step explanation:
If a fair owner makes $18 for a group of 3 people, then the amount per person is 18 ÷ 3 = 6. The rate is $6.
The answer is Y= 2.95-10x